2014
DOI: 10.1254/jphs.14r13cp
|View full text |Cite
|
Sign up to set email alerts
|

History of the G Protein–Coupled Receptor (GPCR) Assays From Traditional to a State-of-the-Art Biosensor Assay

Abstract: Abstract. The G protein-coupled receptors (GPCRs) form the largest and the most versatile superfamily that share a seven-transmembrane-spanning architecture. GPCR-signaling is involved in vision, taste, olfaction, sympathetic/parasympathetic nervous functions, metabolism, and immune regulation, indicating that GPCRs are extremely important therapeutic targets for various diseases. Cellular dielectric spectroscopy (CDS) is a novel technology that employs a label-free, real-time and cell-based assay approach for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 30 publications
(54 reference statements)
2
40
0
Order By: Relevance
“…This study demonstrated that the PTX-sensitive G i/o subunits, especially G o and G i3 , play important roles in the activation of ERK evoked by amitriptyline. The CellKey TM assay confirmed the pharmacological and siRNA findings, in that the pattern of the change in impedance induced by amitriptyline was similar to that of activation of G i/o -coupled receptors, and not of G s -or G q -coupled receptors (13,14,17,18). Although the C6 cells is an astrocyte model cell line derived from rat glioma, activation of the MMP/FGFR/FRS2␣/ERK cascade occurs in both normal human and rat astrocytes as well (9,11), in a PTX-sensitive manner.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…This study demonstrated that the PTX-sensitive G i/o subunits, especially G o and G i3 , play important roles in the activation of ERK evoked by amitriptyline. The CellKey TM assay confirmed the pharmacological and siRNA findings, in that the pattern of the change in impedance induced by amitriptyline was similar to that of activation of G i/o -coupled receptors, and not of G s -or G q -coupled receptors (13,14,17,18). Although the C6 cells is an astrocyte model cell line derived from rat glioma, activation of the MMP/FGFR/FRS2␣/ERK cascade occurs in both normal human and rat astrocytes as well (9,11), in a PTX-sensitive manner.…”
Section: Discussionsupporting
confidence: 62%
“…The G ␣ family of G proteins is composed of the G s , G i/o , and G q subfamilies (14). Among the G protein inhibitors used in this study, only PTX inhibited amitriptyline-induced GDNF production and the amitriptyline-mediated response of the cascade (FRS2␣ and ERK), indicating that PTX-sensitive G i/o plays a critical role in the intracellular response to amitriptyline.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…With regard to the neuropeptides, it is important to distinguish G protein subunits with different functional consequences. Based on the amino acid sequence homologies of Gα subunit, G proteins are classifi ed into Gαs (Gs), Gαi/o (Gi/o), Gαq (Gq) (Miyano et al 2014). Gs protein activates adenylate cyclase (AC) that induces an increase in the intracellular concentration of cyclic adenosine monophosphate (cAMP) and activation of protein kinase A (PKA).…”
Section: Neuropeptide Action On G Protein-coupled Receptorsmentioning
confidence: 99%